Travel, Coal, and Empire: Delineations of Formosa in Nineteenth-Century English Travelers’ Coal Texts - Lu, Li-Ru (SARE: Southeast Asian Review of English, 2018)
Prior to the mid-nineteenth century, Formosa (now Taiwan), was little known to European and American travelers. There was a great abundance of coal, both north and south of the island; as a fuel that could be excavated relatively easily and of value, coal impelled the entry into Formosa of Western explorers, navy investigators, merchants, and naturalist scientists beginning in the mid-nineteenth century. These travelers went on to document the island’s virtually unknown landscapes and natural resources, including its coal. This paper focuses on the “coal texts” of six nineteenth-century English travelers who visited Formosa between 1840 and 1895 — Lieut. M. Gordon (1818-1848), Robert Swinhoe (1836-1877), Cuthbert Collingwood (1826-1908), Cyprian Arthur Bridge (1839-1924), Archibald Ross Colquhoun (1848-1914), and James H. Stewart-Lockhart (1858-1937). It explores the historical and cultural underpinnings of coal in the island’s eco-geopolitical history and is interested to examine the ways these travel writings represented Formosa’s coal mines. It addresses the following questions: How might these coal narratives reveal an environmental consciousness embedded in the history of imperial excavation? What might be the links between nineteenth-century imperial motivations and representations of Formosan coal?